Appraisal of complementarity of subsurface drip fertigation and conservation agriculture for physiological performance and water economy of maize - Patra, K.; Parihar, Chiter Mal; Nayak, Harisankar; Rana, B.; Sena, Dipaka Ranjan; Anand, A.; Reddy, K. S.; Chowdhury, M.; Pandey, R.; Kumar, A.; Singh, L. K.; Ghatala, M. K.; et al. (Elsevier, 2023)
The Indo-Gangetic Plains (IGP) in north-west (NW) India are facing a severe decline in ground water due to prevalent rice-based cropping systems. To combat this issue, conservation agriculture (CA) with an alternative crop/s, such as maize, is being promoted. Recently, surface drip fertigation has also been evaluated as a viable option to address low-nutrient use efficiency and water scarcity problems for cereals. While the individual benefits of CA and sub-surface drip (SSD) irrigation on water economy are well-established, information regarding their combined effect in cereal-based systems is lacking. Therefore, we conducted a two-year field experiment in maize, under an ongoing CA-based maize-wheat system, to evaluate the complementarity of CA with SSD irrigation through two technological interventions–– CA+ (residue retained CA + SSD), PCA+ (partial CA without residue + SSD) – at different N rates (0, 120 and 150 kg N ha-1) in comparison to traditional furrow irrigated (FI) CA and conventional tillage (CT) at 120 kg N ha-1. Our results showed that CA+ had the highest grain yield (8.2 t ha-1), followed by PCA+ (8.1 t ha-1). The grain yield under CA+ at 150 kg N ha-1 was 27% and 30% higher than CA and CT, respectively. Even at the same N level (120 kg N ha-1), CA+ outperformed CA and CT by 16% and 18%, respectively. The physiological performance of maize also revealed that CA+ based plots with 120 kg N ha-1 had 12% and 3% higher photosynthesis rate at knee-high and silking, respectively compared to FI-CA and CT. Overall, compared to the FI-CA and CT, SSD-based CA+ and PCA+ saved 54% irrigation water and increased water productivity (WP) by more than twice. Similarly, a greater number of split N application through fertigation in PCA+ and CA+ increased agronomic nitrogen use efficiency (NUE) and recover efficiency by 8–19% and 14–25%, respectively. Net returns from PCA+ and CA+ at 150 kg N ha-1 were significantly higher by US$ 491 and 456, respectively than the FI-CA and CT treatments. Therefore, CA coupled with SSD provided tangible benefits in terms of yield, irrigation water saving, WP, NUE and profitability. Efforts should be directed towards increasing farmers’ awareness of the benefits of such promising technology for the cultivating food grains and commercial crops such as maize. Concurrently, government support and strict policies are required to enhance the system adaptability.